Przeobrażenia gospodarcze w Polsce w latach 1989-2016 - Leszczyński, Dariusz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article has two purposes, to describe situations of transition. One is to identify the distinctive features of the Polish transformation which may explain why the initial, transformational recession implementation of the economic system. The other objective is to discuss the reforms and policies needed for Poland to continue the process of catching up with the most advanced countries transformation has given citizen. what changes occur for the better. What led to the change and what were the results. a summary of the transformation after 25 years. show a deep analysis of the situation in the EU, plans for the future growth and economic plans of the new government.